CONSUMER BEHAVIOR IN MAKING DECISIONS TO BUY COFFEE AT COFFEE SHOP IN BOGOR CITY - Amellinda, Raisa; Syarief, Rizal; Wulandari, Ririn (Jurnal Doktor Manajemen (JDM), 2023)
Brand Image, coffee shop atmosphere and service quality are factors that influence consumer behaviour in purchasing decisions. This research is located Bogor City focusing on coffee shop using a sample of 112 millennial and Z generations. The data collected by distributing questionnaires. Furthermore, the data that has been collected was analyzed using descriptive analysis and Partial Least Square analysis. The results of this study indicate that brand image does not affect consumers purchase intention of coffee products in Bogor city coffee shops, brand image and service quality have a significant positive effect on consumer purchasing decisions of coffee products in Bogor city coffee shops, Atmosphere coffee shop and service quality have a significant positive effect on purchase intention of consumers of coffee products in coffee shops in Bogor and purchase intentions do not significantly mediate the effect of brand image, Atmosphere coffee shop, and service quality on consumer purchasing decisions for coffee products in coffee shops in Bogor.